Copper–Carbene Intermediates in the Copper‐Catalyzed Functionalization of OH Bonds. Issue 27 (26th May 2015) - Pereira, Ana; Champouret, Yohan; Martín, Carmen; Álvarez, Eleuterio; Etienne, Michel; Belderraín, Tomás R.; Pérez, Pedro J.
Abstract Copper–carbene [TpxCuC(Ph)(CO2Et)] and copper–diazo adducts [TpxCu{η1‐N2C(Ph)(CO2Et)}] have been detected and characterized in the context of the catalytic functionalization of OH bonds through carbene insertion by using N2C(Ph)(CO2Et) as the carbene source. These are the first examples of these type of complexes in which the copper center bears a tridentate ligand and displays a tetrahedral geometry. The relevance of these complexes in the catalytic cycle has been assessed by NMR spectroscopy, and kinetic studies have demonstrated that the N‐bound diazo adduct is a dormant species and is not en route to the formation of the copper–carbene intermediate.